Advances in the Application of Infrared in Food Processing for Improved Food Quality and Microbial Inactivation - Christian K. Anumudu; Helen Onyeaka; Chiemerie T. Ekwueme; Abarasi Hart; Folayemi Isaac-Bamgboye; Taghi Miri (Foods)
Food processing is a fundamental requirement for extending the shelf life of food products, but it often involves heat treatment, which can compromise organoleptic quality while improving food safety. Infrared (IR) radiation has emerged as a transformative technology in food processing, offering a rapid, energy-efficient method for inactivating microbial cells and spores while preserving the nutritional and sensory attributes of food. Unlike traditional heating methods, IR technology enhances heating homogeneity, shortens processing time, and reduces energy consumption, making it an environmentally friendly alternative. Additionally, IR processing minimizes water usage, prevents undesirable solute migration, and maintains product quality, as evidenced by its effectiveness in applications ranging from drying fruits and vegetables to decontaminating meat and grains. The advantages of IR heating, including its precise and even heat diffusion, ability to retain color and nutrient content, and capacity to improve the microbial safety of food, position it as a promising tool in modern food preservation. Nevertheless, there are gaps in knowledge with respect to optimal application of IR in foods, especially in the maintenance product quality and the impact of factors such as IR power level, temperature, wavelength (λ), food depth, and target microorganisms on the applicability of this novel technology in food systems. Recent research has attempted to address challenges to the application of IR in food processing such as its limited penetration depth and the potential for surface burns due to high energy which has delayed the widespread utilization of this technology in food processing. Thus, this review critically evaluates the application of IR in food safety and quality, focusing on factors that affect its effectiveness and its use to moderate food quality and safety while comparing its advantages/disadvantages over traditional thermal processing methods.